Production and Characterization of Bio-Chars and Bio-Oils Formed by Pyrolysis of Persian Hogweed (Heracleum persicum Desf.) in A Fixed-Bed Reactor - Aysu, Tevfik (Journal of Applied Solution Chemistry and Modeling, 2013)
Pyrolysis of Persian Hogweed (Heracleum persicum Desf.) stalks were performed in a fixed-bed tubular reactor with (K2CO3, ZnCl2) and without catalyst at three different temperatures (400, 500 and 600 oC) with a constant heating rate of 50 oC/min. and with a constant sweeping gas (N2) flow rate of 100 cm3/min. The amounts of bio-char, bio-oil and gas produced were calculated and the compositions of the obtained bio-oils were characterized by GC-MS. The effects of pyrolysis parameters such as temperature and catalyst on the product yields were investigated. According to the results, both temperature and catalyst had significant effects on the conversion of Heracleum persicum Desf. into bio-chars, bio-oils and gaseous products. The highest bio-oil yield of 41.42% by weight including aqeous phase was achieved with 10% potassium carbonate catalyst at 500 oC. 71 different compounds were identified by GC-MS in the bio-oils obtained at 500 oC.